The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/su12072988
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Fly Ashes from Fluidized Bed Combustion: A Review

Abstract: Traditionally fly ash is thought to be glassy, spherical particle originating from pulverized coal combustion (PCC) at temperature up to 1700 °C. However, nowadays fluidized bed combustion (FBC) technology is spreading quickly around the world as it is an efficient and environmentally friendly method. FBC is also able to utilize mixtures of low-grade solid fuels (e.g., coal, lignite, biomass, and waste) that have fluctuating quality, composition, and moisture contents. However, this leads to a high variation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 177 publications
(255 reference statements)
2
51
0
Order By: Relevance
“…Moreover, it has been found that smaller the size of fly ash particles higher will be the concentration of heavy metals on their surface i.e., larger fly ash particles will have lesser amount of heavy metals and other elements on their surface than the small-sized fly ash particles [69,70]. In a thermal power plant, there are two types of ashes; bottom ash and fly ash [71]. Bottom ash is generally larger in size and hence there is possibility of lesser concentrations of heavy metals on their surface [72] while the fly ash is finer in size, so comparatively there will be higher concentrations of heavy metals on their surface [72].…”
Section: Inductively Coupled Plasma Analysis Of Fly Ash Digested Samplementioning
confidence: 99%
“…Moreover, it has been found that smaller the size of fly ash particles higher will be the concentration of heavy metals on their surface i.e., larger fly ash particles will have lesser amount of heavy metals and other elements on their surface than the small-sized fly ash particles [69,70]. In a thermal power plant, there are two types of ashes; bottom ash and fly ash [71]. Bottom ash is generally larger in size and hence there is possibility of lesser concentrations of heavy metals on their surface [72] while the fly ash is finer in size, so comparatively there will be higher concentrations of heavy metals on their surface [72].…”
Section: Inductively Coupled Plasma Analysis Of Fly Ash Digested Samplementioning
confidence: 99%
“…Despite the fact that this type of waste is nearly free of nitrogen, it contains substantial amounts of other micro (B, Fe, Mo, Mn, Cu, Zn, Co) and macronutrients, both primary (P, K) and secondary (S, Mg, Ca, Na) [20], which are highly favorable in maintaining appropriate conditions conducive for plant growth. Ohenoja et al [21], for instance, in their broad study on the utilization potential of biomass fly ash where they reviewed at least 46 research papers, confirmed the low content of contaminates in most ash derived from the fluidized bed combustion of pure biomass and satisfactory levels of macronutrients such as phosphorus and calcium, thus concluding the high feasibility of using it as a soil amendment. Moreover, the agronomic effects of using biomass fly ash derived from a variety of feedstocks and combusting technologies on crop yields were also reported by several authors [22][23][24][25].…”
Section: Introductionmentioning
confidence: 94%
“…Fly ash produced from bituminous coal, is mostly acidic even though it has higher sulfur content, while alkaline fly ash is produced from the sub-bituminous coal, which has lower sulfur content, and has higher Ca and Mg content than that derived from bituminous coal [49]. Similarly the electrical conductivity (EC) of fly ash varies between 0.177 to 14 S/m, which directly corresponds to the quantitative concentration of soluble cations and anions in the fly ash [2,50]. Likewise, mineralogy and chemical composition too depend on the various parameters of coal combustion.…”
Section: Chemical Properties Of Fly Ashmentioning
confidence: 99%
“…%) [7,53,54]. The chemical composition of the core or interior part of the fly ash is almost masked by the depositions of elements on the surface layer of fly ash particles [2]. Moreover, these surface layers get depositions of various elements during volatilization and condensation of molten slag in the furnace [55].…”
Section: Chemical Properties Of Fly Ashmentioning
confidence: 99%